Sociodemographic and residential factors associated with multimorbity: results of Brumadinho Health Project - Mary Anne Nascimento-Souza; Josélia Oliveira Araújo Firmo; Paulo Roberto Borges de Souza Júnior; Sérgio Viana Peixoto (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: To evaluate the prevalence of multimorbidity and sociodemographic and residential factors associated with this condition among adults living in Brumadinho, Minas Gerais. Methods: Cross-sectional study with baseline data from the Brumadinho Health Project, conducted in 2021 and comprising 2,777 individuals aged 18 years and over. The outcome variable was multimorbidity, defined by the existence of two or more of 20 chronic diseases. The exploratory variables were sex, age group, educational level, skin color and area of residence according to the dam failure. The association between exploratory variables and multimorbidity was assessed by logistic regression. Results: The prevalence of multimorbidity was 53.8% (95%CI 50.6-56.9). A greater chance of multimorbidity was found among women (adjusted OR=2.5; 95%CI 1.9-3.2), in participants aged between 40 and 59 (adjusted OR=2.8; 95%CI 1.8-4.3) or 60 years and older (adjusted OR=7.9; 95%CI 4.7-13.4) and in residents of the areas that were directly affected by the dam failure (adjusted OR=1.6; 95%CI 1.3-2.0). Conclusion: The burden of multimorbidity on the population of Brumadinho requires effective preventive measures and actions to the whole population, but mainly to the most vulnerable groups, that is, women, middle-aged and older individuals, and those directly affected by the dam failure, in addition to a timely provision of health care to reverse this situation.